Кыдёкын - а инвис?: пиналъёслы повестьёс / Герман Ходырев - Ходырев Герман Алексеевич (Удмуртия, 2001)
Экземпляры: ф.2 (2003) / Инвентарный номер: 36335 / Цена: 77.00 / Авт.знак: Х 69 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)